Use of Preoperative Submucosal Dexamethasone in Third Molar Surgery: A Step towards Improvement in Quality of Life - Shad, Samia -; Mahmud, Akif; Shahnawaz, Adil -; Shah, Syed Majid Hussain; Farooq, Amber -; Khan, Saqib Mehmood; Gillani, Rabia Rahat (Journal of Ayub Medical College Abbottabad, 2021)
Background: Surgical removal of impacted mandibular third molar is one of the most common procedures performed by Oral surgeons globally. The objective of the study was to ascertain the efficacy of pre-operative administration of submucosal dexamethasone on post-operative sequelae in surgically extracted impacted mandibular third molar. It was a double-blind randomized controlled clinical trial that was performed in the Department of Oral & Maxillofacial Surgery at Abbottabad International Dental Hospital, Abbottabad from March 2019 to March 2020. Methods: A total of 150 patients were divided into two groups, each having 75 patients. Group A received a placebo after administration of local anesthesia whereas, group B received 4mg submucosal dexamethasone. A post-operative visit was scheduled after 48 hours to evaluate pain, facial swelling, and Trismus. Results: On the second postoperative day, the patients in the experimental group presented with significantly reduced pain, facial swelling, and trismus in comparison to the control group. Conclusion: Pre-operative administration of 4mg dexamethasone through the submucosal route is efficacious in the reduction of post-operative pain, swelling, and trismus in mandibular third molar surgery thus enabling the patient to return to daily life activities earlier. Keywords: Quality of Life; Dexamethasone; Third Molar Surgery; Swelling; Trismus